1999
DOI: 10.1046/j.1440-1681.1999.03161.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF PYRUVATE ON INTRACELLULAR Ca2+ REGULATION IN CARDIAC MYOCYTES FROM NORMAL AND DIABETIC RATS

Abstract: 1. Pyruvate has been shown to enhance the contractile performance of cardiac muscle when provided as an alternative substrate to glucose. The aims of the present study were to determine whether the inotropic effects of pyruvate are due to increased mobilization of intracellular Ca2+ ([Ca2+]i) and to compare the effects of pyruvate on [Ca2+]i levels in myocytes from normal and diabetic animals. 2. Fura-2 was used to monitor [Ca2+]i in ventricular myocytes isolated from control and streptozotocin-treated male Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Early studies reported an increase in resting Ca 2ϩ (23), whereas Noda et al (24) reported a reduced basal Ca 2ϩ in diabetic cardiomyocytes. Several reports demonstrated no differences in basal Ca 2ϩ or peak Ca 2ϩ levels between diabetic and control cardiomyocytes (25)(26)(27), which is consistent with our results. Therefore, there may not be significant alteration of Ca 2ϩ levels that correspond to the depressed contraction in diabetic cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Early studies reported an increase in resting Ca 2ϩ (23), whereas Noda et al (24) reported a reduced basal Ca 2ϩ in diabetic cardiomyocytes. Several reports demonstrated no differences in basal Ca 2ϩ or peak Ca 2ϩ levels between diabetic and control cardiomyocytes (25)(26)(27), which is consistent with our results. Therefore, there may not be significant alteration of Ca 2ϩ levels that correspond to the depressed contraction in diabetic cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Now, it is clear that there are at least three different kinds of Ca 21 channels in plasmic membrane: voltage-dependent (VDCC), receptor-operated (ROCC), and store-operated Ca 21 channel (SOCC). VDCC is activated by membrane depolarization, which was related to high K 1 -induced Ca 21 influx [Ethier et al, 2001;Fukao et al, 2001;Katsuyama et al, 1991;Mellors et al, 1999;Liu et al, 2001], whereas ROCC is regulated by activation of plasma membrane receptors, which was related to glutamate-induced increase in free cytosolic Ca 21 [De-Erausquin et al, 1990;Dessi et al, 1992]. The store-operated Ca 21 channel's (SOCC) activation is [Putney et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in ⌬G ATP impair calcium handling (sarcoplasmic reticulum Ca 2ϩ -ATPase) and crossbridge cycling (actin-myosin ATPase) (16), critical steps in force-generating contraction. Pyruvate has been shown to increase sarcoplasmic reticular Ca 2ϩ uptake and release while increasing both energy state and contractile performance in isolated perfused hearts (6,23,27) and cardiomyocytes (28,31).…”
Section: Discussionmentioning
confidence: 99%